2020
DOI: 10.1101/2020.10.15.341719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

K29-Linked Ubiquitin Signaling Regulates Proteotoxic Stress Response and Cell Cycle

Abstract: Protein ubiquitination, one of the most common posttranslational modifications, is involved in numerous cellular processes. It shows remarkable topological and functional diversity, a phenomenon known as the ubiquitin code, through the polymerization of ubiquitin via different linkages. Deciphering the cellular ubiquitin code is of central importance to understanding the physiology of the cell. Among the eight possible linkages, K29-linked polyubiquitin is a relatively abundant type of polyubiquitin in both hu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 72 publications
(108 reference statements)
3
6
0
Order By: Relevance
“…This data which implicates K29-linked ubiquitylation during cell cycle progression, also revealed the presence of K29 linkages in mitotic cells, specifically at the midbody during telophase. In line with our data, HECTD1 and BUB3 were identified from pulldown and proteomics analysis using the K29-specific affimer [50]. This exciting new reagent now enables further studies to explore and the function of ubiquitin chains containing K29 linkages in various cellular context including during cell cycle progression.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This data which implicates K29-linked ubiquitylation during cell cycle progression, also revealed the presence of K29 linkages in mitotic cells, specifically at the midbody during telophase. In line with our data, HECTD1 and BUB3 were identified from pulldown and proteomics analysis using the K29-specific affimer [50]. This exciting new reagent now enables further studies to explore and the function of ubiquitin chains containing K29 linkages in various cellular context including during cell cycle progression.…”
Section: Discussionsupporting
confidence: 79%
“…In this study we explored HECTD1 function in the context of cell proliferation and found that loss of HECTD1 ubiquitin ligase activity reduces cell proliferation through an effect on mitosis. Together, our data support recent evidence implicating K29-linked ubiquitylation in mitotic regulation and provide novel insights into the 'ubiquitin code' [50].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Where indicated, cells were pre‐extracted prior to fixation using either CSK buffer (100 mM NaCl; 10 mM HEPES; 3 mM MgCl 2 ; 300 mM sucrose; 0.25% Triton‐X; 1 mM PMSF) or a stringent pre‐extraction buffer (10 mM Tris‐HCl, pH 7.4; 2.5 mM MgCl 2 ; 0.5% igepal; 1 mM PMSF). K29‐linked Ub conjugates were visualized using a K29‐Ub‐specific synthetic antigen binder (sAB‐K29; kind gift from Minglei Zhao (University of Chicago)) (Yu et al , 2021) and Alexa Fluor 488 AffiniPure F(ab′)2 Fragment Donkey Anti‐Human IgG (Jackson Immunoresearch). Local UV damage was induced by irradiating cells on coverslips with 100 J/m 2 through a PBS‐equilibrated membrane of 8 μm pores and fixing at the indicated timepoints.…”
Section: Methodsmentioning
confidence: 99%
“…Lys27-linked chains appear important for regulating innate immunity [ 41 ], cell cycle [ 42 ], and mitochondrial functions [ 43 ]. Finally, Lys6-chains have been described to participate in DNA repair [ 44 ] and mitophagy [ 45 ], whereas, Lys29-chains have been associated with Wnt signaling [ 46 ], and just recently, proteotoxic stress and cell cycle [ 47 ]. Lys33-chains play a crucial role in post-Golgi trafficking [ 48 ] and T-cell receptor (TCR) regulation [ 49 , 50 ].…”
Section: Protein Ubiquitinationmentioning
confidence: 99%